The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ange.202005207
|View full text |Cite
|
Sign up to set email alerts
|

Tighter Confinement Increases Selectivity of d‐Glucose Isomerization Toward l‐Sorbose in Titanium Zeolites

Abstract: Aqueous-phase isomerization of d-glucose to d-fructose and l-sorbose is catalyzed in parallel by Lewis acidic Ti sites in siliceous frameworks.G lucose isomerization rates (per Ti,3 73 K) are undetectable when Ti sites are confined within mesoporous voids (Ti-MCM-41, TiO 2-SiO 2) and increase to detectable values when Ti sites are confined within the smaller 12-membered ring (12-MR) micropores of Ti-Beta. Isomerization rates decrease to lower values (by % 20)with further decreases in micropore sizeasT isites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…This may because, at low pH, H + competes with metal cations for the same adsorption position [68]. When the pH increased, the ability of H + to combine adsorption sites decreased, while positively charged strontium ions began to occupy adsorption sites on the surface of the adsorbent and therefore the adsorption capacity increased [69]. However, other studies showed that when the pH increased further (>9), due to the presence of a large number of anions in water, metal ions are surrounded by anions, forming negatively charged atomic groups that reduce the adsorption effect of strontium ions [70,71].…”
Section: Effect Of Phmentioning
confidence: 99%
“…This may because, at low pH, H + competes with metal cations for the same adsorption position [68]. When the pH increased, the ability of H + to combine adsorption sites decreased, while positively charged strontium ions began to occupy adsorption sites on the surface of the adsorbent and therefore the adsorption capacity increased [69]. However, other studies showed that when the pH increased further (>9), due to the presence of a large number of anions in water, metal ions are surrounded by anions, forming negatively charged atomic groups that reduce the adsorption effect of strontium ions [70,71].…”
Section: Effect Of Phmentioning
confidence: 99%